Education as an Effort to Humanize Humans: A Philosophical Study with a Descriptive Qualitative Approach - Hasnah Faizah; Nuratikah Nuratikah; Kartika Sari; Farra Addina; Ikrom Ihlasul (Global Education : International Journal of Educational Sciences and Languages, 2025)
Education is fundamentally a process of developing the whole person, not simply the transfer of knowledge. This research aims to examine the essence of education as an effort to humanize humans through a descriptive qualitative approach using a literature study method. This concept emphasizes that education plays a central role in developing students' potential, awareness, and human values. This study explores the thoughts of figures such as Paulo Freire, Ki Hajar Dewantara, and John Dewey, who positioned education as a path to liberation and humanity. The analysis shows that true education must be oriented toward developing human values, morals, and character to avoid becoming trapped in the process of dehumanization amidst technological developments and modernization. Through literature review and thematic analysis, this research found that humanistic education must integrate rationality, morality, and spirituality to form complete human beings. Thus, education must be understood as a continuous process of humanization to build a civilized, ethical, and just society.